Fiberoptic endoscopic examination of swallowing with simultaneous ice pack test in patient with myasthenia gravis: A case report - Tomohiko Yamauchi; Ayano Ono; Takeharu Kanazawa (Acta Oto-Laryngologica Case Reports, 2023)
AbstractMyasthenic crisis (MC) is a life-threatening complication of myasthenia gravis (MG), affecting 15–20% of patients with MG at least once. The rapid and accurate diagnosis of MG is mandatory but challenging because patients with MC require intubation and mechanical ventilation or noninvasive ventilation (NIV). We describe a case of an 81-year-old woman diagnosed with MG related dysphagia. Simultaneous fiberoptic endoscopic examination of swallowing (FEES) and ice-pack test (FEES-ice pack test) revealed a significant decrease in pharyngeal residue, suggesting MG. The day following the test, she experienced respiratory failure. FEES-ice pack test results and respiratory distress suggested MC. NIV followed by mechanical ventilation was started quickly, leading to improved respiratory condition. We show that the FEES-ice pack test led to prompt treatment for MC. Although further investigations are required for sensitivity, specificity, and positive criteria, the FEES-ice pack test could be a safe and easy method to diagnose MG.